Crystal structure of benzyl(methyl)phenyl[(piperidin-1-ium-1-yl)methyl]silane bromide - Barth, Eva Rebecca (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, C(20)H(29)NSi(+)·Br(−), contains a chiral silicon atom but crystallizes as a racemate. The C—Si—C bond angles in the range of 103.64 (8)–111.59 (9)° are usual for tetrahedral geometry. The piperidine ring shows a regular chair conformation with an equatorially positioned exocyclic N—C bond. In the crystal, there is a hydrogen bond between the ammonium cation and the bromide anion. The crystal packing shows the dominant intermolecular interaction to be the electrostatic attraction between the ammonium cation and the bromide anion.